(untitled) (Bangladesh Journal of Zoology, 2015)
Composition and abundance of zooplankton in a polyculture pond was studied during June 2003 to May 2004. A total of 33 major species of zooplankton including 11genera of Rotifera, 4 of Copepoda, 4 genera of Cladocera and 2 genera of Protozoa were identified. The monthly abundance of zooplankton varied form 4228 indiv/l in October 2003 to169 indiv/l in January 2004. Among the total zooplankton, Rotifera comprised of 71.07%, Copepoda comprised of 12.49% Nauplii comprised of 11.96%, Cladocera comprised of 1.49% and Protozoa comprised of 2.99%. Water temperature (r = 0.18), free CO2 (r = 0.40), TDS (r = 0.14) and water depth (r = 0.55) showed positive correlation with zooplankton but air temperature, pH, dissolved O2, total hardness and ammonia showed negative correlation (the coefficients being -0.18, -0.05, -0.25, -0.38 and -0.11 respectively) with the occurrence of zooplankton. The average growth of fishes and zooplankton showed positive correlation in all cases but the relations were insignificant when tested statistically. Bangladesh J. Zool. 42(1): 67-76, 2014